Γ-Alumina-supported Pt17 cluster: controlled loading, geometrical structure, and size-specific catalytic activity for carbon monoxide and propylene oxidation. Issue 2 (2nd January 2020) - Negishi, Yuichi; Shimizu, Nobuyuki; Funai, Kanako; Kaneko, Ryo; Wakamatsu, Kosuke; Harasawa, Atsuya; Hossain, Sakiat; Schuster, Manfred E.; Ozkaya, Dogan; Kurashige, Wataru; Kawawaki, Tokuhisa; Yamazoe, Seiji; et al.
Abstract : A Pt17 cluster was precisely loaded on γ-alumina and the resulting Pt17 /γ-Al2 O3 exhibited high catalytic activity for CO and C3 H6 oxidation. Abstract : Although Pt is extensively used as a catalyst to purify automotive exhaust gas, it is desirable to reduce Pt consumption through size reduction because Pt is a rare element and an expensive noble metal. In this study, we successfully loaded a Pt17 cluster on γ-alumina (γ-Al2 O3 ) (Pt17 /γ-Al2 O3 ) using [Pt17 (CO)12 (PPh3 )8 ]Cl n ( n = 1, 2) as a precursor. In addition, we demonstrated that Pt is not present in the form of an oxide in Pt17 /γ-Al2 O3 but instead has a framework structure as a metal cluster. Moreover, we revealed that Pt17 /γ-Al2 O3 exhibits higher catalytic activity for carbon monoxide and propylene oxidation than γ-Al2 O3 -supported larger Pt nanoparticles (PtNP /γ-Al2 O3 ) prepared using the conventional impregnation method. Recently, our group discovered a simple method for synthesizing the precursor [Pt17 (CO)12 (PPh3 )8 ]Cl n . Furthermore, Pt17 is a Pt cluster within the size range associated with high catalytic activity. By combining our established synthesis and loading methods, other groups can conduct further research on Pt17 /γ-Al2 O3 to explore its catalytic activities in greater depth.